Pelimpahan Hutang terhadap Ahli Waris: Perspektif Hukum Positif dan Hukum Islam - Abd. Holik (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
This study analyzes the transfer of a deceased person's debt to heirs from the perspectives of positive law (Indonesian Civil Code) and Islamic law. Under the Indonesian Civil Code, heirs automatically receive the rights and obligations of the deceased, including debts, but have the option to renounce the inheritance, thereby freeing themselves from debt liability. In contrast, under Islamic law, the transfer of debt (hiwalah) is obligatory for those capable of assuming it, and delaying payment by a financially capable individual is considered an act of injustice (zalim). This study aims to compare these two legal perspectives on the responsibility of heirs for the deceased's debts and their implications. Employing a qualitative normative legal research method with a literature review approach, secondary data from the Al-Qur'an, Hadith, Indonesian Civil Code, and relevant legal literature are analyzed. The findings reveal significant differences in approaches between positive law and Islamic law regarding the option of inheritance renunciation and the implications of debt. Islamic law places a stronger emphasis on the absolute obligation to settle debts for the welfare of the deceased, heirs, and creditors, while positive law offers more flexibility to heirs.